The weekend effect – How can it be mitigated? Introduction of a consultant-delivered emergency general surgical service. (September 2020) - Somasundram, Khevan; Neville, Jonathan J.; Sinha, Yashashwi; Agarwal, Tushar; Raje, Durgesh; Sinha, Ashish; Sheth, Hemant
Abstract: Background: Poorer patient outcomes for emergency general surgery have been observed in patients admitted to hospital over the weekend. This paper reports the outcomes of a Consultant-delivered service model for weekend admissions and its impact for patients undergoing emergency laparotomy. Methods: Operative data was analysed from a prospectively collected database over 5-years. Primary outcome measures were 30-day all-cause mortality and Clavien-Dindo class ≥2 morbidity. Secondary outcomes included time from admission to diagnostic imaging and time to surgery, post-operative length of stay and requirement for Intensive Care Unit admission. Results: 263 patients underwent an emergency laparotomy. Overall 30-day mortality was 4.6% and all-cause morbidity was 55.9%. The most common indications for laparotomy were mechanical small bowel obstruction (32.7%) and hollow viscus perforation (30.4%) of the 263 emergency laparotomies, 92 patients in the cohort were weekend admissions (Saturday or Sunday). There was no significant difference amongst patients admitted during the weekend in ASA grade, age, gender, or proportion of patients receiving a pre-operative computed tomography scan, when compared to those during the week. Compared to weekdays, weekend admission was not associated with a significant difference in mortality (5.3% and 3.3%, respectively p = 0.458), all-cause morbidity (p = 0.509), post-operative length of stay (p = 0.681), or Intensive Care Unit admission (p = 0.761). Conclusion: A Consultant Surgeon delivered emergency service can avoid the poor patient outcomes associated with weekend admissions and the 'weekend effect'. Highlights: Poorer patient outcomes have been observed in patients admitted during the weekend. A Consultant Surgeon delivered model of service delivery ensures peri- and intra-operative Consultant presence for all emergency surgery. Under this model, there was no weekend effect observed.